A MATLAB software platform for modelling vertically-integrated non-hydrostatic flows with moment equations. (May 2020) - Gamero, Pedro; Bergillos, Rafael J.; Cantero-Chinchilla, Francisco N.; Castro-Orgaz, Oscar
Abstract: This work presents a software platform to compute depth-integrated non-hydrostatic coastal and open channel flows. The software is based on the V ertically-A veraged and M oment (VAM) equations model. The VAM model uses the weighted residual method to account for the non-hydrostaticity and non-uniformity of flow. After presenting the governing equations, numerical scheme and structure of the graphical user interface, the software is applied to solve coastal and open channel flow tests with significant non-hydrostaticity and non-uniformity of flow. The results are compared with hydrostatic model computations and laboratory measurements. Where a hydrostatic-based simulation poorly reproduces experimental observations, the higher-order model equations by this software platform generate excellent predictions. These findings highlight the potential of this user-friendly software platform for modeling open channel, river and nearshore flows and processes, where non-hydrostatic pressure and non-uniform velocity shall be accounted for, which entails a meaningful advance for the hydraulic community. Highlights: A software platform to compute depth-integrated non-hydrostatic flows is presented. The software is based on the Vertically-Averaged and Moment equations model. The software is applied to solve several open channel and coastal flow tests. Excellent agreements are obtained between the software results and experimental data.